2018
DOI: 10.1016/j.conb.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Wired for eating: how is an active feeding circuitry established in the postnatal brain?

Abstract: From birth, mammals have to find food and maximize caloric intake to ensure growth and survival. Suckling must be initiated quickly after birth and then maintained and controlled until weaning. It is a complex process involving interactions between sensory and motor neuronal pathways. Meanwhile, the control of food intake and energy homeostasis is progressively established via the development of hypothalamic circuits. The development of these circuits is influenced by hormonal and nutritional signals and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…There is a high level of conservation of these genes, as a colinear set, across multiple vertebrates, including the mouse, in which 28 of the 32 minimally critically deleted genes are found adjacent to one another on murine Chromosome 16 (Meechan et al, 2015). There is remarkable homology of the colinear set of 22q11-deleted genes in multiple species, and their cellular, developmental, and homeostatic functions in a broad range of cells, tissues, and organs appear to be similar in most vertebrates -and even some invertebrates -analyzed thus far (Meechan et al, 2015;Motahari et al, 2019). A key aspect of 22q11 gene function across these species may be the apparent relationship to neural crest, and non-axial M/E signaling at midgestation, and its consequences for subsequent morphogenesis and neural circuit development.…”
Section: A B Cmentioning
confidence: 99%
See 3 more Smart Citations
“…There is a high level of conservation of these genes, as a colinear set, across multiple vertebrates, including the mouse, in which 28 of the 32 minimally critically deleted genes are found adjacent to one another on murine Chromosome 16 (Meechan et al, 2015). There is remarkable homology of the colinear set of 22q11-deleted genes in multiple species, and their cellular, developmental, and homeostatic functions in a broad range of cells, tissues, and organs appear to be similar in most vertebrates -and even some invertebrates -analyzed thus far (Meechan et al, 2015;Motahari et al, 2019). A key aspect of 22q11 gene function across these species may be the apparent relationship to neural crest, and non-axial M/E signaling at midgestation, and its consequences for subsequent morphogenesis and neural circuit development.…”
Section: A B Cmentioning
confidence: 99%
“…Rather than a few 22q11 deleted genes, we found that 21/28 are expressed selectively at these sites based upon qPCR analysis in micro-dissected samples of each M/E inductive site as well as whole mount in situ or immunolabeling ( Figure 5). None of the 22q11 genes is known to selectively alter neural crest specification or migration (Motahari et al, 2019). Instead, many of these genes, including several candidates for specific 22q11DS phenotypes, seem to modulate either local patterning, differentiation, or signaling.…”
Section: Location Location Location: Restricted Expression and Actimentioning
confidence: 99%
See 2 more Smart Citations
“…In rodents, connections between "homeostatic" hypothalamic nuclei and the LHA are not fully established at birth and mature over the first weeks postnatally, making them susceptible to changes in the perinatal nutritional environment (Muscatelli and Bouret, 2018). Projections from the ARC to the DMH mature by postnatal day (PND) 6, whereas those reaching the PVN and the LHA are observed between PND8-10 and PND12, respectively (Bouret et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%